The Utilization of Physical Education Learning Media in Increasing The Active Learning Time of Elementary School Students - Sutarjo, Sutarjo; Hadiwinarto, Hadiwinarto (Jurnal Basicedu, 2022)
The purpose of this study was to obtain a description of "Utilization of Physical Education Learning Media in an Effort to Increase Students' Active Learning Time". The method used in this research is The Classroom Action Research. The design used in this study is a cyclical model which includes the steps of planning, implementing, observing, and reflecting. The population used by purposive sampling, as many as 32 fourth grade students. The instrument used is in the form of field notes (Duration Recoding), namely the use of active time to learn physical education through observation with an average of 60% so that the target achievement is determined with an average of 90%. Based on research in cycle I (Actions I, II and III) 90.43%, because it has exceeded the research target, it is completed in cycle II. Based on the results of data analysis, it is concluded that the use of physical education learning media is quite significant in increasing the active learning time of students at SDN 01 Kec. Madang Tribe 1 Kab. OKU EAST